The impact of health sector‐wide approaches on aid effectiveness and infant mortality. (27th May 2021) - Woode, Maame Esi; Mortimer, Duncan; Sweeney, Rohan
Abstract: The effectiveness of health aid remains contested. Previous estimates fail to distinguish between fragmented, poorly‐targeted aid and aid disbursed under aid effectiveness principles. To address this gap, we investigated whether the sector‐wide approach (SWAp), a mechanism for aid delivery built on aid effectiveness principles, has delivered improvements in aid effectiveness and infant mortality. Results suggest that SWAp implementation facilitated a 5.8% to 8.1% reduction in the infant mortality rate compared to non‐implementing countries. This effect likely operates by releasing domestic resources and/or increasing the efficiency with which domestic resources are converted into health gains. Development partners should take heart that the aid effectiveness agenda appears to have paid dividends in the health sector.